Colloidal PbSe quantum dot-filled liquid-core optical fiber for temperature sensing. (17th April 2019) - Zhang, Zhongyang; Wang, Yu; Jiang, Yongheng; Feng, Yi; Wang, Helin; Zhang, Tieqiang; Zhuang, Xingwei; Zhang, Jia; Ma, Yue; Xing, Xiaoxue; Yu, Siyao; Yu, William W
Abstract: Precisely acquiring real-time temperature is always a significant task in various areas. With their distinct temperature-dependent optical properties, PbSe quantum dots are a promising thermosensitive material. We packed colloidal PbSe quantum dot solution into optical fibers for temperature measurement. The temperature-dependent photoluminescence intensity of PbSe quantum dots was studied with the variation of particle size, solution concentration and sensitive area length. The temperature sensitivity was found to be 0.01 V °C −1 in a temperature range from −80 to +100 °C and the relative deviation was less than 4%.